Blood transfusion: hospital negligence / Siti Radziah Kamarudin … [et al.] - Kamarudin, Siti Radziah; Shaharil, Mohd Hezri; Haron, Nur Hafiza; Abdul Rauf, Noor Fazlina (Faculty of Law, 2005)
Every year, over 100 million blood units (one unit is a half-litre pouch) are collected from donors worldwide. But millions mere are still needed. The World Health Organisation (WHO) estimates that annually as many as 150,000 women die in childbirth due to lack of blood supply or inappropriate blood therapy.1 According to WHO, as much as five percent of HIV infections in developing countries may be caused by transfusion of contaminated blood. We sometimes happened to read in the local newspaper that a patient becomes a victim of medical malpractice. Only a few victims have brought the cases to the court to claim for compensation. After a while the case will hardly been heard or read in the mass media. In contrast, the western civilian such as the Americans and English are more aware of their rights in medical negligence. As part of the public we must aware about the procedures, types of disease that can be transmitted, responsibilities and rights of every parties involved in conducting a blood transfusion. The Ministry of Health has played a major role to set up a law and guidelines for the medical practitioners to reduce any possibility of transmitting contaminated blood but still more cases appeared. Yet an agent to the ministry must be more aware of their liability such as hospitals, doctors and nurses. The blood donor also must be more responsible for their action to use blood bank as a place to test their blood for any infection.